THE IMPLEMENTATION OF PICTURE SERIES MEDIA TO IMPROVE PGMI ’S STUDENTS ABILITY IN SPEAKING - RIRIS NUR KHOLIDAH (Universitas Islam Negeri Sumatera Utara, 2016)
The problems of this research were how to improve speaking ability using series of picture and how to motivate the students to speak English. The research was guided by a conceptual framework leading to the using series of pictures through pair work to improve their motivation to speak English during the process of classroom communication interaction. The research type was an action research. The subject consisted of 20 students of PGMI 2014/2015 academic years. The research data were collected using test (test after first treatment and test after the second treatment), observation for collecting data on the students’ motivation in improving speaking ability using series pictures. Data on speaking ability using series of picture were analyzed using the descriptive and statistic analysis, using the increasing of mean after the first and the second treatment. The study concluded that using series of pictures through pair work as a teaching strategy variation has brought a new nuance in English language teaching in improving their ability to speak English